PENERAPAN METODE PEMBELAJARAN TALKING STICK UNTUK MENINGKATKAN PRESTASI BELAJAR IPS - Sari, Ida Ayu Putu Purnama (Universitas Tabanan, 2023)
This research was a classroom action research which aimed to find out the extent of the application of the Talking Stick Learning Method to class VIII D students of SMP Negeri 1 Kerambitan in the Academic Year 2021/2022. To achieve this goal, the Talking Stick Learning Method was implemented to the class VIII D students of SMP Negeri 1 Kerambitan in the academic year 2021/2022, consisting of 32 students. The object of the research was the IPS learning achievement and the learning completeness. The IPS learning achievement data was collected by using the learning achievement test. Meanwhile, the students’ learning completeness was obtained by comparing the students' daily test scores with the KKM scores (KKM score = 72). If the grades obtained by the students had reached the KKM or more, then the students were declared complete, and if they had not reached the KKM, they were declared incomplete. The percentage of the students who had achieved the KKM or more stated classical completeness. Furthermore, the data collected in this study was analyzed descriptively. The results of this study indicated that after implementing the Talking Stick learning method, there was an increase in the IPS students' learning achievement, namely in the cycle I with the average score of 71.25 and in the cycle II it increased into 80.94. Meanwhile, the students’ learning completeness in the cycle I was 53.13% increased in the cycle II which reached 96.88%.